Floating Texts: Listening Practices in the Accounts of Foreign River Expeditions in Brazil - Fernando G. Cespedes (Humanities)
Western written travel narratives are a byproduct of the privileging of vision as the primary means of knowledge production, an epistemology often imposed on indigenous peoples through colonial practices. In contrast, indigenous cultures in Brazil have long relied on listening as a central way of engaging with their environment. In the present essay, I examine how listening practices appear in the written accounts produced by members of three foreign river expeditions in Brazil from the 16th to the 20th century. I analyzed travel accounts from Gaspar de Carvajal’s Relación del Nuevo Descubrimiento del Famoso Río Grande (XVI century), Hercules Florence’s Voyage Fluvial du Tieté à l’Amazone (XIX), and Theodore Roosevelt’s In the Jungles of Brazil (XX). To explore what these travelers might have heard, I also collaborated with a sound designer to create a soundscape using actual recordings of local fauna and indigenous chants and music. The results show a variety of listening modes put into practice such as conquest-driven, scientific observation, contemplation, and hunting-focused and aesthetic appreciation. These narratives illustrate how European epistemologies reinforced Western dominance by shaping both colonial encounters and scientific approaches to Brazilian wilderness exploration.